Determination of isoflavones in soybean food and human urine using liquid chromatography with electrochemical detection - Klejdus, Borivoj; Vacek, Jan; Adam, Vojtech; Zehnálek, Josef; Kizek, René; Trnková, Libuse; Kubán, Vlastimil (Journal of chromatography. B, Analytical technologies in the biomedical and life sciences, 2004)
A highly sensitive high-performance liquid chromatographic method with electrochemical detection (HPLC-ED) was developed for the determination of isoflavones. Electrochemical behaviour of daidzein and genistein was studied on carbon paste electrode (CPE) by adsorptive transfer stripping square wave voltammetry. The obtained electrochemical results were used for the development of HPLC-ED method. Furthermore, isoflavones were separated on an Atlantis dC18 column using a mobile phase consisting of acetonitrile (solvent A) and 0.15M acetate buffer of pH 5.5 (solvent B) at a flow rate 0.4 mL/min. A linear gradient profile (solvent B) was at 0-2 min 87%; 22 min 60%; 27 min 50%; 31 min 45%; 47 min 87%. Full scan of multi-channel coulometric detection was tested and optimal potential at 450 mV was chosen for our purposes. Calibration curves were linear (daidzein R(2) = 0.9993 and genistein R(2) = 0.9987). The detection limit for daidzein/genistein was 480/394 pg/mL (1.8/1.5 nM) and per column 2.4/1.9 pg. Isoflavones extracted from soybean products (farina, meat, milk) by the accelerated solvent extraction (ASE) procedure and isoflavones present in human urine were determined by the HPLC-ED method.
Keywords: Glycine max; senzitivita a specificita; Electrochemistry; isoflavony; Reproducibility of Results; Sensitivity and Specificity; Chromatography, High Pressure Liquid; Isoflavones; Calibration; Humans; spektrofotometrie ultrafialová; Spectrophotometry, Ultraviolet; reprodukovatelnost výsledků; elektrochemie; kalibrace; vysokoúčinná kapalinová chromatografie; lidé